Learners' Online Self-Regulated Learning Skills in Indonesia Open University: Implications for Policies and Practice - Harry B. Santoso; Rahayu Dwi Riyanti; Trini Prastati; FA. Triatmoko H. S.; Arie Susanty; Min Yang (MDPI AG, 2022)
To succeed in online distance learning where students are physically separated from teachers and peers, students must develop self-regulated learning skills to effectively manage their learning process. This study examined how students with different demographic backgrounds adopt or fail to adopt self-regulated learning to engage in online distance learning. Survey data were collected from 295 students at Indonesia Open University. Although students' online learning self-efficacy and online self-regulated learning were above average, they reported low levels of confidence and abilities to seek help, develop task strategies, and allocate time for online learning. Their online self-regulated learning and online learning self-efficacy were significantly correlated. However, there were no significant relationships between online self-regulated learning and learning performance, and between online learning self-efficacy and learning performance. Furthermore, female and/or older students reported lower learning performance than male and younger students. Qualitative data from open-ended questions were analyzed to interpret the quantitative results. Recommendations for stakeholders of open universities were made to assist in students' improvement of self-regulated learning skills and to address equity issues in Indonesian online distance learning and similar contexts.